PENENTUAN PERCEPATAN GRAVITASI PADA PERCOBAAN GERAK JATUH BEBAS DENGAN MEMANFAATKAN RANGKAIAN RELAI - Haris Rosdianto (Spektra: Jurnal Fisika dan Aplikasinya, 2017)
The determination of the gravity acceleration through free fall experiment using the relay circuit has been done. This study aims to make free-fall experiment design using relay circuit, and determine the value of gravity acceleration by using this experiment design. The measurement method used in this study is to measure the free fall time of the object using a stopwatch that can work automatically. The result of this research is this experiment design can be used to get the free fall time data automatically. The values of gravity acceleration to 10 cm, 20 cm, 30 cm, 40 cm and 50 cm respectively, are 9.80952381 m/s2, 9.814058957 m/s2, 9.845 m/s2, 9.858283385 m/s2, and 9.829645226 m/s2. So that the average acceleration value of the five variations of height is 9.831302275 m/s2. Keywords: Free fall motion, gravity acceleration, relay circuit.